Determinants of Stunting in Indonesian Toddlers - Resty Jayanti; Galuh Pradian Yanuaringsih; Nina Olivia; Kipa Jundapri; Shanti Ariandini; Rindasari Munir (Institute of Medico-legal Publications Pvt Ltd, 2021)
Children who are malnourished for a long time can experience a failure to thrive, namely stunting.Thissituation occurs in many developing countries such as Indonesia. Stunting is a linear growth disordercharacterized by a TB/U z-score less than -2SD. The study aimed to examine the incidence of stunting inchildren under five in terms of exclusive breastfeeding (ASI), complementary foods of breast milk (MPASI),immunization status, family characteristics. The research approach is quantitative with a Case-ControlStudy design and is carried out in West Java Province, with a sample size of 120 people. Data analysisincludes bivariate using Chi-Square. The results showed that the incidence of stunting in children underfive was due to low family income (p = 0.004; OR= 9.33), non-exclusive breastfeeding (p= 0.001; OR=28.5), poor complementary feeding (p= 0.001; OR= 16), and incomplete immunization (p = 0.00; OR = 17).Stunting in children under five is closely related to low family income, non-exclusive breastfeeding, poorcomplementary breastfeeding, and incomplete immunization. Meanwhile, non-exclusive breastfeeding is adominant factor as a risk factor for children experiencing stunting.